REGIONAL ACTORS' ROLE IN THE AFGHAN PEACE PROCESS (Journal of the Spanish Institute for Strategic Studies, 2021)
On February 29th, the United States and the Taliban signed an agreement that, if successful, will end with the signing of a peace agreement between the insurgent group and the Afghan government. For the negotiations that are now beginning to prosper, the support of the regional powers is essential. Predicting the attitude they can adopt as the process progresses requires analysing the initial position of each of them, their interests in Afghanistan, what they can expect from a possible peace agreement and, above all, what they would never accept. In fact, finding a balance between all these interests, which are often opposed, is one of the keys to the ongoing process.
Keywords: Afghanistan Peace Agreement, India-Pakistan Conflict, US Withdraw from Afghanistan, South-East Asia.